THE USE OF BIG HERO SIX MOVIE WITH SUBTITLES TO TEACH VOCABULARY IN SENIOR HIGH SCHOOL - Nur Tri Lestari; Elis Homsini Maolida (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2018)
Abstract This research entitled “The Use of Big Hero Six Movie with Subtitles to Teach Vocabulary in Senior High School”.The vocabulary learning is important and indispensable part of any language learning process to the learners. However, current teachers’ methods of teaching vocabulary seem not to be so effective that the quality is far from being satisfactory. In this case, the application of movies is considered one of the effective ways to teach vocabulary to the learners. Therefore, it is essential to get teachers and students to be familiarized with this relaxing but useful technique. This research intends to examine the use of movies to teach vocabulary form students. The research was carried out in SMA ISLAM AL-MAZIYAH at 10-3 class as a subject in the study. Qualitative method was applied and for triangulation purpose three data collection techniques were chosen such as observation, questionnaire and interview. The observation was conducted two times. To complete the data, the researcher used observation sheet during the learning process in the class. Beside that, the researcher used lesson  plan  to answer the first research question. Then, the questionnaire was conducted to answer second research question. To support the data, the questionnaire results were analysed after the observation. After the questionnaire the researcher used interview to answer the third research question, to complete the data the interview was conducted to the teacher. The result of study shows that the students is enthusiastic learning vocabulary through movie. Movie is good for facilitating thinking and problem solving, movie can be used in big class, students are naturally exposed to the myriad of authentic speech forms of the target language,  it is simple and it helped the students to acquire new vocabularies that they never found in their student books. However, the teacher have a difficulties to teach vocabulary through movie. Such as, poor facility of the school copyright restriction of the movie, movie takes too much time, educational part may only be a small portion of the overall, movie may turn teacher and students become passive and movie requires more preparation. Key word : Movies, Vocabulary.